PENGARUH TINGKAT SALAFIYAH TERHADAP PERSPEKTIF SANTRI TENTANG RADIKALISME DI PONDOK PESANTREN AL FAQIH - AKHMAD TAUFIQ, DKK, AKHMAD TAUFIQ, DKK (Program Magister Ilmu Politik, Universitas Diponegoro, 2011)
AbstractAfter collapse the World Trade Center, make terrorism rumors and religious radicalism,especially islam is central rumors and be international attention. In indonesia, rumors about terrorismand religious radicalism is attention many sides after Balinese Bomb I and Balinese Bomb II. Of somuch many religious terror events, executant predominantly from circle santri Pondok PesantrenSalaf. This study has deskriftif-kuantitatif, that is study to realize certain phenomenon and elaboratedby using number score or rank. Result from this study mentions, that study system at salafiy influentialtowards Islamic fanaticism so strong in self Santri. Santri’s opinion that Islam religion that must theyfight for and distribute to society variously. Perspective of santri about religious radicalism is onlyaround that aspect. In other aspect, like nationalism, jihad, and their attitude is towards hebrewperson and christian within measure standart.Keyword: The Pondok Pesantren Salaf, Religious Radicalism, Islamic Fanatism